2015
DOI: 10.7224/1537-2073.2014-037
|View full text |Cite
|
Sign up to set email alerts
|

Use of Accelerometers to Measure Real-Life Physical Activity in Ambulatory Individuals with Multiple Sclerosis

Abstract: Background: Multiple sclerosis (MS) may negatively affect individuals' participation in physical activity (PA). We used accelerometers to determine PA level in individuals with MS with varying degrees of disability as measured by the Expanded Disability Status Scale (EDSS) during regular daily activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…[32] and Romberg et al [33] for European pwMS, but well above those found in several investigations performed in the United States [34][35][36][37][38]. In the latter, the number of daily steps ranged from 5800 to 7698, depending on the average level of participants' disability.…”
Section: Discussionsupporting
confidence: 56%
“…[32] and Romberg et al [33] for European pwMS, but well above those found in several investigations performed in the United States [34][35][36][37][38]. In the latter, the number of daily steps ranged from 5800 to 7698, depending on the average level of participants' disability.…”
Section: Discussionsupporting
confidence: 56%
“…After examining titles and abstracts of these studies, 217 studies were included for full‐text review. Reasons for the exclusion of 185 of these studies are outlined in Figure and 32 studies remained in the review . Of those 32 studies, 25 were included for meta‐analysis and allowed comparison to the NHANES database.…”
Section: Resultsmentioning
confidence: 99%
“…41 A wide range of PA outputs were measured. Activity counts were measured in 22 studies, 5,18,20,21,25,27,28,[30][31][32][33][34][35][36][37][39][40][41][44][45][46]48 step counts in 10 studies, [18][19][20]26,29,34,[44][45][46][47] minutes of MVPA in three studies 23,38,44 minutes of light PA in one study, 23 minutes of dynamic activity in one study, 42 minutes of sedentary time in one study, 23 and energy expenditure in two studies. 22,24 The outputs of step counts and minutes of MVPA were metaanalyzed and compared to published NHANES data.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with higher self-efficacy are more likely to set out self-care behaviors and tend to be more adhering to that beneficial behavior ( 7 ). Furthermore, there has been a significantly reverse relationship reported between perceived self-efficacy, depression and anxiety and intensity of pain felt by patients with multiple sclerosis ( 13 , 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%